Extreme Phenotypic Plasticity in Metabolic Physiology of Antarctic Demosponges - Morley, Simon A.; Berman, Jade; Barnes, David K. A.; de Juan Carbonell, Carlos; Downey, Rachel V.; Peck, Lloyd S. (Frontiers in Ecology and Evolution, 2016)
Seasonal measurements of the metabolic physiology of four Antarctic demosponges and their associated assemblages, maintained in a flow through aquarium facility, demonstrated one of the largest differences in seasonal strategies between species and their associated sponge communities. The sponge oxygen consumption measured here exhibited both the lowest and highest seasonal changes for any Antarctic species; metabolic rates varied from a 25% decrease to a 5.8 fold increase from winter to summer, a range which was greater than all 17 Antarctic marine species (encompassing 8 phyla) previously investigated and amongst the highest recorded for any marine environment. The differences in nitrogen excretion, metabolic substrate utilisation and tissue composition between species were, overall, greater than seasonal changes. The largest seasonal difference in tissue composition was an increase in CHN (Carbon, Hydrogen and Nitrogen) content in Homaxinella balfourensis, a pioneer species in ice-scour regions, which changed growth form to a twig-like morph in winter. The considerable flexibility in seasonal and metabolic physiology across the Demospongiae likely enables these species to respond to rapid environmental change such as ice-scour, reductions in sea ice cover and ice-shelf collapse in the Polar Regions, shifting the paradigm that polar sponges always live “life in the slow lane”. Great phenotypic plasticity in physiology has been linked to differences in symbiotic community composition, and this is likely to be a key factor in the global success of sponges in all marine environments and their dominant role in many climax communities.